Tight Cutting Seton for Anal Fistulae Revisited - Edgaras Smolskas (World Journal of Colorectal Surgery)
Background: Anal fistulas are a common medical problem affecting thousands of patients annually well over 2000 years. There are many new novel approaches to this old condition but none with overwhelming success and low complication rates. The aim of this retrospective review was to revisit our experience in the treatment of anal fistulas with a tight cutting seton.